2019
DOI: 10.1002/hpm.2799
|View full text |Cite
|
Sign up to set email alerts
|

Identification and ranking of specific balanced scorecard performance measures for hospitals: A case study of private hospitals in the Klang Valley area, Malaysia

Abstract: Summary Performance measurement is a necessity for private hospitals as they need to be efficient, attract customers, increase profitability, and survive in the competitive environment of the health care industry. Hospitals typically struggle to identify appropriate performance measures because of lack of reliable source of performance measures for private hospitals. Despite numerous studies on performance measurement, few studies have focused on performance measures in private hospitals. This paper aims to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 23 publications
(22 reference statements)
0
33
1
2
Order By: Relevance
“…The hospital management needs to involve employees more often in hospital activities so that a more optimal working relationship between management and employees can be established and organizational goals can be achieved together. These results are different from that of a study which reported that all indicators of this perspective have achieved the maximum results [1,29]. However, some studies revealed that all indicators of this perspective have not shown the maximum results [11,30].…”
Section: Discussioncontrasting
confidence: 96%
“…The hospital management needs to involve employees more often in hospital activities so that a more optimal working relationship between management and employees can be established and organizational goals can be achieved together. These results are different from that of a study which reported that all indicators of this perspective have achieved the maximum results [1,29]. However, some studies revealed that all indicators of this perspective have not shown the maximum results [11,30].…”
Section: Discussioncontrasting
confidence: 96%
“…It follows that it is necessary to reduce the operating costs through evaluation and improvement of internal hospital processes. Due to the growing demands for quality improvement and the increasing pressure from regulatory agencies, issues regarding how to provide high-quality hospital services and improve patient satisfaction have caught the attention of hospital administrators [ 1 , 2 ]. Specifically, an efficient hospital sterilization process (HSP) ensures that reusable medical devices (RMDs) are more rapidly available for healthcare activities.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, TQM promises much for service industries, yet it has been little used in healthcare [6]. According to Komashie et al [7], this is due to several reasons: (1) the large differences between the two sectors in terms of concerns for quality and the type of processes and outputs involved, (2) the fact that quality researchers have differing views toward the best approaches, and (3) the fact that consumers of healthcare have little knowledge about their needs, unlike in those of industries. There is therefore little historical evidence of healthcare consumers demanding any level of quality.…”
Section: Introduction 1research Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, there has been great change in the construction of healthcare systems [1,2]. Due to the growing demands for quality improvement and the increasing pressure from regulatory agencies, problems on how to provide high-quality medical services and improve patient satisfaction have caught the attention of hospital administrators [3,4]. The assessment and measurement of healthcare performance play a great part in hospital management and can significantly affect the operational efficiency of a healthcare management system [5,6].…”
Section: Introductionmentioning
confidence: 99%